Both autologous bone marrow mononuclear cell and peripheral blood progenitor cell therapies similarly improve ischaemia in patients with diabetic foot in comparison with control treatment. Issue 5 (5th July 2013) - Dubsky, M.; Jirkovska, A.; Bem, R.; Fejfarova, V.; Pagacova, L.; Sixta, B.; Varga, M.; Langkramer, S.; Sykova, E.; Jude, E. B.
Abstract Background The aim of our study was to compare the effect of bone marrow mononuclear cell and peripheral blood progenitor cell therapies in patients with diabetic foot disease and critical limb ischaemia unresponsive to revascularization with conservative therapy. Methods Twenty‐eight patients with diabetic foot disease (17 treated by bone marrow cells and 11 by peripheral blood cell) were included into an active group and 22 patients into a control group without cell treatment. Transcutaneous oxygen pressure and rate of major amputation, as the main outcome measures, were compared between bone marrow cells, peripheral blood cell and control groups over 6 months; both cell therapy methods were also compared by the characteristics of cell suspensions. Possible adverse events were evaluated by changes of serum levels of angiogenic cytokines and retinal fundoscopic examination. Results The transcutaneous oxygen pressure increased significantly (p < 0.05) compared with baseline in both active groups after 6 months, with no significant differences between bone marrow cells and peripheral blood cell groups; however, no change of transcutaneous oxygen pressure in the control group was observed. The rate of major amputation by 6 months was significantly lower in the active cell therapy group compared with that in the control group (11.1% vs. 50%, p = 0.0032), with no difference between bone marrow cells and peripheral blood cell. A number of injected CD34+ cells and serum levels of angiogenic cytokines after treatment did not significantly differ between bone marrow cells and peripheral blood cell. Conclusions Our study showed a superior benefit of bone marrow cells and peripheral blood cell treatments of critical limb ischaemia in patients with diabetic foot disease when compared with conservative therapy. There was no difference between both cell therapy groups, and no patient demonstrated signs of systemic vasculogenesis. Copyright © 2013 John Wiley & Sons, Ltd.